Internal And External Radiation Exposure Evaluation Amongst Selected Workers And Locations In Iraq - Abdullah, Ammar Abid (2013)
There are many changes that have affected badly the environment and people’s life in Iraq during the last two decades as a result of wars and suspected used of prohibited weapons and what ways these reveal dangerous diseases. The objectives of the present work was to measure the uranium concentration in urine taken from workers in factories and hospitals by using Fission Track Analysis (FTA) technique, analyze the specific activities of radionuclides analysis in soil using high purity germanium (HPGe) detector, and determining radon concentration in air using Nuclear Track Detectors (NTDs) LR-115 type II. Also, Alphaguard water borne radon detector was used to determine radon concentration in water samples. Air, water and soil samples were taken from factories and hospitals in selected regions of Iraq after the 2003 Gulf war. The results shown that the highest uranium concentration was 3.39±0.43 μg/L for urine samples of workers from the Phosphate factory and the lowest uranium concentration was 1.31±0.24 μg/L for X-ray workers in hospitals. The uranium concentration in the urine samples increases with number of working years. The uranium concentration in urine samples of male, sick, addicted and smoking workers are higher than female, healthy, non addicted and non smoking workers, respectively. Soil samples from the Phosphate factory have the maximum values of Raeq, Hin, Hex, ADRA, and the annual effective indoor and outdoor doses were 744.71 Bq/kg, 4.07, 2.06, 353.39 nGy/h, 1.734 and 0.433, respectively compared to other factories and hospitals.